The future of energy security of states - Jarosław Jerzy Gryz (Security and Defence Quarterly, 2020)
The work focuses on the controversy about technological progress and unlimited access to all kinds of energy acquisition, storage and distribution. It suggests a formula for energy acquisition and usage which embraces issues of peace and war, social conflicts, and stability determined by access to energy conditioned by the state of the climate of our planet. The question is how will an interdisciplinary combination of progress and future implementation of technologies influence energy security of states and social entities, their natural environment, up to 2030 and beyond? The methods used in the work rely on a non – linear approach to disruptive technologies combined with empirical verifiability of scientific progress in the field of energy acquisition and use. They are reinforced with drivers taken from development scenarios gained through technological development in quantum mechanics, molecular biology, and computational techniques. The result is a conceptual approach to energy acquisition and distribution for states, their communities and individuals regardless of whether the technologies are “civil” or “military” in their essence. The recalled disruptive technologies shape factors of social development and create conditions for human existence and the natural environment that influence the security of states and social entities. The development of automation and robotics, digital transformation, bio-technologies and cognitive science creates new energy security for states, social entities and the natural environment. Technologies for the generation, processing and distribution of energy create an almost unlimited perspective of reconfiguration of existing forms of life and their safety.